2009
DOI: 10.1002/j.2168-9830.2009.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

An Engineering Major Does Not (Necessarily) an Engineer Make: Career Decision Making Among Undergraduate Engineering Majors

Abstract: This study uses a mixed-methods design to investigate students' career decision making at two U.S. undergraduate institutions. The research question was, "To what extent do students who complete undergraduate programs in engineering intend to pursue engineering careers?" We surveyed senior engineering majors about their post-graduate intentions, and later interviewed a subset of the seniors about their career intentions. Only 42 percent of students surveyed reported that they definitely intended to pursue a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 14 publications
7
109
0
Order By: Relevance
“…20 Still other studies have drawn attention to the disproportionate impact of internships on engineering students, including in terms of predicting increased retention in engineering degree programs, as a factor in career decision-making, and as a key mechanism for development of professional competence, to name a few salient themes. 21,22,23 Looking beyond the engineering education literature, one can also find engineers as subjects in broader studies of college-to-career transitions. 24 Andrew's accounts of his educational and work experiences also open a small but insightful window into professional engineering work, confirming what scholars of professional practice have been suggesting for quite some time, namely "that the social and technical are almost inextricably tied up together" 13 (p. 120).…”
Section: Discussionmentioning
confidence: 99%
“…20 Still other studies have drawn attention to the disproportionate impact of internships on engineering students, including in terms of predicting increased retention in engineering degree programs, as a factor in career decision-making, and as a key mechanism for development of professional competence, to name a few salient themes. 21,22,23 Looking beyond the engineering education literature, one can also find engineers as subjects in broader studies of college-to-career transitions. 24 Andrew's accounts of his educational and work experiences also open a small but insightful window into professional engineering work, confirming what scholars of professional practice have been suggesting for quite some time, namely "that the social and technical are almost inextricably tied up together" 13 (p. 120).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as the civil engineering discipline grew as a profession, so did the reasons for formally educating future civil engineers. As undergraduate engineering educators, we hope that students obtain the necessary competencies to enter into the engineering workforce; however, it is also important that students begin to align and negotiate their identities with those of the profession to create their own professional identity throughout their educational experiences [22,[34][35][36] . In this section, we describe three key disciplinary advancements and their influences on civil engineering education: 1) the development of the American Society for Civil Engineers (ASCE) Body of Knowledge, 2) establishment of professional credentialing systems, and 3) the creation of the ASCE Code of Ethics.…”
Section: Historical Influences Of the Disciplinary Professionalizatiomentioning
confidence: 99%
“…Work by Lichtenstein et al found that a minority percentage (42%) of seniors definitively planned on pursuing an engineering related career following graduation. 12 Undergraduate engineering programs must try to do better to foster engineering identity development so that professional persistence is improved and the workforce is provided a steady stream of capable degreed engineers from a variety of backgrounds.…”
Section: Professional Engineering Identitymentioning
confidence: 99%